Prey adaptive behaviour under predation risk modify stoichiometry predictions of predator‐induced stress paradigms. (24th March 2018) - Guariento, Rafael Dettogni; Luttbeg, Barney; Carneiro, Luciana Silva; Caliman, Adriano
Abstract: Prey responses to predation risk can affect multiple phenotypic traits that have significant implications for population‐to‐ecosystem‐level properties. The general stress paradigm (hereafter GSP) proposes integrating the principles of ecological stoichiometry and prey physiological plasticity in response to predation risk to provide an explicit mechanistic framework to evaluate the direct influence of predation risk on ecosystem functioning. However, theoretical attempts evaluating the GSP have focused on only one component of phenotypic plasticity, neglecting the fact that multiple phenotypic responses can affect nutrient demand and consumption, and therefore, the overall animal effect on nutrient cycling rates and stoichiometry. In this study, we used a dynamic state variable model to examine how variation in predation and starvation risk on a landscape of patch types that vary in food quality affects the behavioural and physiological phenotypic responses of prey and the linked nutrient and carbon recycling. We found that the stress imposed by predation risk promotes prey carbon limitation, which leads to increased nutrient release and carbon uptake due to a stoichiometric mismatch between an animal's demand and food stoichiometry. Such effects can be altered by prey shifting spatially to carbon‐ or nutrient‐rich patches. However, the abilities of prey to cope with new physiological demands can be affected by absolute stress level or the predation risk distribution on a spatially implicit landscape of stoichiometric‐divergent patch type availability. Overall, starvation risk can act as a selective force favouring individuals that maximize their growth, thus reducing their nutrient release, but increasing their exposure to predation risk. Our results provide an important connection between predator‐induced stress ecology and ecosystem functioning, linking organism nutrition and ecological stoichiometry to fitness outcomes, thus improving our understanding of how non‐consumptive predator effects can scale up to ecosystems. A plain language summary is available for this article. Abstract : Plain Language Summary